Modelling Airline Operations at Major Commercial Airports for Strategic Decision Support - Smith, L. Douglas; Bilir, Canser (Transportation Development Research, 2024)
The authors discuss an integrated modelling approach for improving flight operations at major commercial airports. Statistical models, built with microdata from hundreds of thousands of flights, are embedded in a process-oriented discrete-event simulation model with two-dimensional geo-spatial characteristics and logical structures based on the concept of staged queues. With results from three application settings, the authors illustrate the wealth of information that this modelling framework can provide for collaborative planning of airport infrastructure and flight operations. Novels about this work are (1) the use of microdata to construct multivariate statistical models for delay propagation at the focal airport and their use to provide time-dependent and situation-dependent parameters for stochastic behaviour in the simulation model, (2) rigorous validation of the simulation model against historical performance, and (3) creation of an integrated analytical platform for strategic decision support.